Emergency Remote Library Instruction and Tech Tools: A Matter of Equity During a Pandemic - Ibacache, Kathia; Rybin Koob, Amanda; Vance, Eric (Information Technology and Libraries, 2021)
During spring 2020, emergency remote teaching became the norm for hundreds of higher education institutions in the United States due to the COVID-19 pandemic. Librarians were suddenly tasked with moving in-person services and resources online. For librarians with instruction responsibilities, this online mandate meant deciding between synchronous and asynchronous sessions, learning new technologies and tools for active learning, and vetting these same tools for security issues and ADA compliance. In an effort to understand our shared and unique experiences with emergency remote teaching, the authors surveyed 202 academic instruction librarians in order to answer the following questions: (1) What technology tools are academic librarians using to deliver content and engage student participation in emergency remote library sessions during COVID-19? (2) What do instruction librarians perceive as the strengths and weaknesses of these tools? (3) What digital literacy gaps are instruction librarians identifying right now that may prevent access to equitable information literacy instruction online? This study will deliver and discuss findings from the survey as well as make recommendations toward best practices for utilizing technology tools and assessing them for equity and student engagement.